Optimasi Proses Expanded Foam Injection Molding Material Eva Foam Untuk Peningkatan Kualitas Produk - Sudrajat, Nugroho Faris; Suhadi, Amin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to optimize the cooling process in Expanded Foam Injection Molding (EFIM) in order to improve the dimensional consistency of EVA foam products. EVA foam, which is widely used in the footwear industry, especially sneakers, is produced through a foaming process in which blowing agents and curing agents are mixed into the EVA polymer. Variations in the cooling process cause significant differences in product size (dimensions), thereby increasing the reject ratio and affecting the final product quality. Using the Taguchi design experiment approach, this study identifies key parameters in the cooling process, such as temperature, time, and cooling rate, and analyzes their effects on product dimensions. The results show that the application of optimal cooling conditions can reduce the reject ratio and produce products with more consistent dimensions. This study contributes to the manufacturing industry.